Mobilidade pedonal e o efeito barreira das rodovias urbanas: as contradições e os conflitos no Anel Rodoviário Celso Mello Azevedo, em Belo Horizonte (MG) - Bárbara Abreu Matos (2022)
The historical prioritization of public policies given to individual motorized modes of transportation has generated (and still generates) significant impacts on mobility and access of the population in urban space. Result of the action of economic and social agents that (re)produce it, based on the interests of the dominant classes, the urban space has been remodeled in an attempt to meet the demand of the flow of vehicles and not the needs of people, leading to the reorganization of the circulation space, opening of new roads and creation of infrastructure to support automobiles, not infrequently potentiating conflicts and contradictions. In this context, transportation infrastructures have commonly become obstacles to mobility and accessibility, especially for people who move by active modes. Their location in the urban environment induces the occurrence of the phenomenon known as "barrier effect", which causes a strong socio-spatial segregation and, consequently, reduce various forms of social contacts, directly impacting the well-being and freedom of movement of residents. This effect materializes more intensely in urban highways, since in these places the high speed of vehicles, the intense volume of traffic and the very infrastructure that breaks the urban fabric, causes the physical separation of communities living in the neighborhoods bordering its margins, as occurs in the Ring Road Celso Mello Azevedo, located in Belo Horizonte (MG). Urban highways also highlight the contradictions and conflicts of use between vehicles and pedestrians, incurring in deprivations of pedestrian travel, affecting the conditions in which pedestrian mobility takes place, increasing risks and accidents during crossings. Given this context, this thesis aims to analyze pedestrian mobility around the Belo Horizonte Ring Road, based on the proposition of mobility, accessibility and crossing risk indicators, as well as a brief reflection on possible conflicts and contradictions imposed on the pedestrian flow in this space. To this end, we propose, first, the estimation of pedestrian crossings between its margins (from two-way intersections) and the identification of the characteristics of pedestrians who make these trips, based on data from the recent historical series of the Origin and Destination Survey of the Metropolitan Region of Belo Horizonte (1992-2002-2012). Subsequently, in possession of the most recent data from the OD Survey of RMBH, the application of the proposed indicators is carried out, correlating them with preponderant factors for the evaluation of the potential risk of crossing, such as vehicle flow, accident rate, socioeconomic characteristics of pedestrians, reasons for access and location of irregular occupations. The results indicate that, throughout the period of analysis, crossing flows were reduced, even in areas where there was population growth. The profile of pedestrians has also changed, with emphasis on changes in the age, gender and income of these people. It was also evident the prevalence of crossings by motorized modes, the inequalities in access to pedestrian bridges and the high risk for pedestrians crossing, a scenario that is reflected in significant occurrences of pedestrian collisions on the highway.